Sunda Clouded Leopard Neofelis diardi (Cuvier, 1823) (Mammalia: Carnivora: Felidae) occupancy in Borneo: results of a pilot vehicle spotlight transect survey - Jephte Sompud; Sze Lue Kee; Kurtis Jia-Chyi Pei; Paul Liau; Collin Goh; Anthony J. Giordano (Wildlife Informaton Liaison Development Society, 2023)
The Sunda Clouded Leopard Neofelis diardi on Borneo is threatened principally by deforestaton for oil palm plantatons and the indiscriminate use of illegal trapping. Sunda Clouded Leopard populatons are decreasing across their range, and the species has been categorised as Vulnerable on the IUCN Red List. Despite the persistence of threats and numerous surveys in recent years, informaton on its ecology is stll limited. Most studies to date have relied on the use of camera traps as their primary sampling tool, as it is challenging otherwise to gather data on Sunda Clouded Leopards. This study aimed to test the feasibility of estmatng the Sunda Clouded Leopard occupancy using a diferent approach. We conducted vehicle spotlight transect surveys in a mixed-use forest reserve and logging concession in Sabah. We drove a cumulatve total of 8,433 km of transects at night and documented the occurrence of Sunda Clouded Leopards in eight out of 31 predetermined long-distance transects, yielding a relatvely low naïve occupancy rate (nO = 0.26). When accountng for imperfect detecton (ρ = 0.15), null occupancy of Sunda Clouded Leopards appeared much higher (ᴪ = 0.55), though our parameter estmates lacked relatve precision. Despite this, our results suggest there may be potental to further refne and adapt a basic, cost-efectve monitoring approach in a local mixed-use reserve with the help of concession managers and additonal improvements to study design. We cauton, however, that not all study sites may be suited for this type of approach and strongly advise the development of pilot studies to evaluate their overall feasibility